ENTOMOFAUNA DO BARUZEIRO: OBSERVAÇÃO E INDENTIFICAÇÃO NO CERRADO-PANTANAL - SANTOS JUNIOR, Benedito Amauri; ZAZYCKI, Luiza Cristiane Fialho; DA SILVA, José Victor; PRADO, Deyvid Martins (ANAIS DO ENIC, 2024)
-